Geography of urban areas in the country of Zab through the flood trip of Al - Abab al - Numeiri - Otman Al-Riahi Palace model - Ziani, Asadik (Milev Journal of Research and Studies, 2018)
This paper discusses the features and forms urbanization of the Architecture in the cities of Zab during the Century 7th - 8th Hijri /13 -14 AD in the source represented in the "Faydh El-Obab" to Ibn Haj Nimeiri; we chose a model for the palaces built by "B’ni Riyah" in the Palace of Othman AlRiyahi.